PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. TETIRA INTERNATIONAL CONSULTANTS - Tzalinggar, Ayudyasiwi; Widiasari, Arifa; Astuti, Desti Mega; Primeri, Novem Gardenia Ninik; Agusti, Ninda Putri Zulekha Sapta; Damayanti, Dila (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
This research aims to analyze the influence of leadership style and work environment on employee performance at PT. TETIRA International Consultants in Jakarta. This research method uses a quantitative (primary) approach in the form of a questionnaire distributed to the entire research population. The population in this study were all employees of PT. TETIRA International Consultants and the samples used were 30 samples. The variables used in this research are the independent variables, namely Leadership Style (X1) and Work Environment (X2) and the dependent variable, namely Employee Performance (Y). The results of the t test (partial test) show that the Leadership Style variable (X1) has a significance value of 0.011 < 0.05, with the results obtained tcount > ttable, namely 2.746 > 1.701. This means the influence of Leadership Style (X1) on employee performance (Y) at PT. TETIRA International Consultants is significant. Meanwhile, the results of the t test (partial test) show that the Work Environment variable (X2) has tcount < ttable, namely 0.339 < 1.701 and has a significant value of 0.737 > 0.05. These results prove that the Work Environment variable (X2) has no significant effect on the employee performance variable (Y) at PT. TETIRA International Consultants. The results of the F Test (Simultaneous Test) show a significant value of 0.000 or the significance value of the F test is smaller than 0.05. This means that the Leadership Style Variable (X1) and Work Environment (X2) simultaneously have a significant effect on the Employee Performance Variable (Y).